2007
DOI: 10.1021/jp0688005
|View full text |Cite
|
Sign up to set email alerts
|

Overtone Spectroscopy of Sulfonic Acid Derivatives

Abstract: Vapor-phase OH-stretching overtone spectra of methanesulfonic acid and trifluoromethanesulfonic acid were recorded in the Deltav(OH) = 4 and 5 regions using cavity ring-down spectroscopy. We compare these spectra to those of sulfuric acid to consider the effect on vibrational overtone spectra of replacing one of the OH groups with a more or less electronegative group. We complement our experimental work with anharmonic oscillator local mode calculations of the OH-stretching frequencies and intensities. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 58 publications
8
59
0
Order By: Relevance
“…37,71,95,118 CRD lengthens the interaction time of the sample and light using high reflectivity mirrors, which contain the laser pulse in the cell with the sample to increase the number of absorption transitions that occur. Two sets of mirrors were necessary to observe the spectra.…”
Section: Crd Spectramentioning
confidence: 99%
“…37,71,95,118 CRD lengthens the interaction time of the sample and light using high reflectivity mirrors, which contain the laser pulse in the cell with the sample to increase the number of absorption transitions that occur. Two sets of mirrors were necessary to observe the spectra.…”
Section: Crd Spectramentioning
confidence: 99%
“…34 Using a simple one-dimensional anharmonic oscillator local model, the overtone spectra of sulfuric acid derivatives have been computed, which found that excitation of the OH-stretching transition with ∆v ≥ 4 and ∆v ≥ 5, will provide sufficient energy for photodissociation of HSO 3 Cl and HSO 3 F, respectively. 29,34,35 Finally, ab initio molecular dynamics (MD) simulations have demonstrated that the decomposition of these derivatives, similar to what has been proposed to H 2 SO 4 , is possible via excitation of higher OH-stretching overtone transitions. 29,34 At the semi-empirical PM3 level, it was found that for HSO 3 Cl, excitation of v ≥ 4, or v ≥ 5 (PM3) can induce the elimination reaction.…”
Section: Introductionmentioning
confidence: 52%
“…29,34,35 Finally, ab initio molecular dynamics (MD) simulations have demonstrated that the decomposition of these derivatives, similar to what has been proposed to H 2 SO 4 , is possible via excitation of higher OH-stretching overtone transitions. 29,34 At the semi-empirical PM3 level, it was found that for HSO 3 Cl, excitation of v ≥ 4, or v ≥ 5 (PM3) can induce the elimination reaction. 34 For photodissociation of HSO 3 F excitation of the v ≥ 7 OH-stretching state is necessary with PM3, whereas excitation of the v ≥ 5 overtone is sufficient at the MP2/TZP level.…”
Section: Introductionmentioning
confidence: 52%
“…A number of further experiments have sought to characterize overtone absorptions for trace compounds where absorption in these bands may be related to reactivity through overtone-induced photolysis. (29) Studies have focused primarily on compounds with O-H stretches, such as organic and inorganic acids, where overtones up to v OH = 5 have been commonly measured (30,31) . A few measurements of C-H overtones in volatile organic compounds have also been made, such as alkanes (32) and highly reactive alkenes, including isoprene.…”
Section: Spectroscopymentioning
confidence: 99%